Design optimization of a superbike paddock stand through integrated CAD and CAE system application / Helmi Rashid, Alias Mohd Saman and Mohammad Azzeim Mat Jusoh - Rashid, Helmi; Mohd Saman, Alias; Mat Jusoh, Mohammad Azzeim (Research Management Institute (RMI), 2013)
A normal design of a superbike paddock stand usually requires two people to lift up the superbike. This contributes to an impractical and inconvenient working scenario for riders when doing maintenance work alone. Therefore a newly designed superbike paddock stand was developed to overcome this problem whereby it managed to demonstrate a new working procedure to help riders to lift up their superbike alone. However there are still rooms for improvements on this newly designed superbike paddock stand that can be optimized. Through this research, the optimizations are established through CAD and CAE system application. The objectives of this research are to optimize a new design of a superbike paddock stand focusing on finite element analysis (FEA) on different size of steel tubing used and to develop a physical prototype for testing and verification purpose. The initial stage of the research methodology is to put up a literature study on types of superbike paddock stand, working procedures of using paddock stands and also suitable materials in fabricating paddock stand. This will be followed by the development of a CAD model replicating the new designed paddock stand to be optimized. A finite element model will be generated from the CAD model to be simulated and analysed using CAE application software. The results from this simulation and analysis will be used to develop a physical prototype for testing and verification purpose on an actual superbike. Outcomes of this research may contribute to a new commercialised design of a superbike paddock stand and improve working procedures for riders that somehow need to do maintenance works alone.